PASTA: PARP activity screening and inhibitor testing assay - Kirby, Ilsa T. (STAR Protoc, 2021)
Small-molecule inhibitors have been instrumental in uncovering the biological importance of poly-ADP-ribose polymerases (PARPs), a family of enzymes involved in wide-ranging aspects of cell biology. However, few PARP inhibitors are tested against the entire family of PARPs. This makes it impossible to confidently assess the role of a single PARP in cellular processes using small molecules. Here, we detail a PARP activity screening and inhibitor testing assay (PASTA) for determining relative selectivity of PARP inhibitors. For complete details on the use and execution of this protocol, please refer to Kirby et al. (2018).